Design of Mini Grid for SHP Plants - Singh, S. N.; Sharma, M. P.; Singh, Ajit (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
The supply of power to remote rural areas in India from Small Hydropower Projects (SHP)/renewable en-ergy power projects in cost effective and sustainable manner requires the optimum design of mini-grids. The present paper deals with the design of mini grids of nine SHP plants presently running in isolated mode only for 8 hrs/day wasting the energy of 16 hrs/day. Based on system layouts, transmission routing, line length and selection of conduc-tor, 5 different alternates of mini-grids were developed to connect these SHPs together as well as with the nearby 33 kV grid substations located at approximately 15, 17 and 9 km from nearby SHPs in order to improve the load factor. The optimization of these alternates on the basis of the Break Even Point (BEP) has indicated that Alternate-V has been found as optimum alternative for the study area with shortest line length, low line losses and minimum capital investment for the mini-grid implementation. Key words: Small Hydropower Project (SHP) station; Mini-grid; Remote rural areas; Break Even Point; India DOI: 10.3126/hn.v7i0.4235 Hydro Nepal Journal of Water, Energy and Environment Vol 7, July, 2010 Page: 38-47 Uploaded date: 31 January, 2011